Differential Responsiveness of the Platelet Biomarkers, Systemic CD40 Ligand, CD62P, and Platelet-Derived Growth Factor-BB, to Virally-Suppressive Antiretroviral Therapy - Steel, Helen C.; Venter, W. D. Francois; Theron, Annette J.; Anderson, Ronald; Feldman, Charles; Arulappan, Natasha; Rossouw, Theresa M. (Frontiers in Immunology, 2021)
Systemic biomarkers of inflammation, including cytokines and chemokines, are potentially useful in the management of both HIV infection and non-AIDS-defining disorders. However, relatively little is known about the utility of measurement of circulating biomarkers of platelet activation as a strategy to monitor the efficacy of combination antiretroviral therapy (cART), as well as the persistence of systemic inflammation following virally-suppressive therapy in HIV-infected persons. These issues have been addressed in the current study to which a cohort consisting of 199 HIV-infected participants was recruited, 100 of whom were cART-naïve and the remainder cART-treated and virally-suppressed. Fifteen healthy control participants were included for comparison. The study focused on the effects of cART on the responsiveness of three biomarkers of platelet activation, specifically soluble CD40 ligand (sCD40L), sCD62P (P-selectin), and platelet-derived growth factor-BB (PDGF-BB), measured using multiplex suspension bead array technology. Most prominently sCD40L in particular, as well as sCD62P, were significantly elevated in the cART-naïve group relative to both the cART-treated and healthy control groups. However, levels of PDGF-BB were of comparable magnitude in both the cART-naïve and –treated groups, and significantly higher than those of the control group. Although remaining somewhat higher in the virally-suppressed group relative to healthy control participants, these findings identify sCD40L, in particular, as a potential biomarker of successful cART, while PDGF-BB may be indicative of persistent low-level antigenemia.